Evaluation of the Histamine Levels of Tuna (Euthynnus Affinis) Based on the Length of Storage and Its Implications for Health - Noor, Thalia Anggrea; Sudaryati, Ni Luh Gede; Widyantari, Anak Agung Ayu Sauca Sunia (Indonesian Journal of Global Health Research, 2024)
Increased histamine levels in tuna (Euthynnus affinis) during storage may pose health risks to consumers. However, the effects of storage duration on histamine levels are not yet fully understood. Objective: This study aimed to evaluate the increase in histamine levels in mackerel based on its duration of storage at 4°C and its implications for public health. Methods: The experimental research had a completely randomized design. This study consisted of 7 treatment groups: negative control, positive control, and storage days 2, 4, 6, 8, and 10. Tuna were collected from the Kedonganan Fish Market and were randomly selected for inclusion in each group. Histamine levels were measured using a spectrophotometric method at a wavelength of 496 nm and analyzed using SPSS (USA, Chicago, IL) version 25.0 at a 95% confidence level (P <0.05). Results: There was a correlation between the length of storage and the increase in histamine levels in tuna (p = 0.001). The histamine levels in tuna on the second day of storage were 46.19 mg/kg, those on the fourth day were 46.57 mg/kg, those on the sixth day were 50.97 mg/kg, those on the eighth day were 54.76 mg/kg, and those on the tenth day were 58.52 mg/kg. The longer the tuna is stored, the higher the histamine levels are. The most striking increase occurred after the sixth day of storage. However, the histamine levels remained within the standard limits set by the government until the 10th day of storage. Conclusion: Storage for 4°C significantly increased histamine levels in tuna. The implications of this study include the need for fish storage management as well as the need for a consumer understanding of health risks due to prolonged fish storage and good fish selection.